The Relationship Service Quality To The Satisfaction Of Mandiri In health Health Insurance Users Visited To Kediri Service Office - Dwianggimawati, Mayta Sari; Yudhana, Amarin; Siyoto, Sandu (Universitas STRADA Indonesia, 2017)
Service quality can mean a simple way to achieve desired goals in the most efficient and effective way, with an emphasis on satisfying the consumer. By knowing the level of customer satisfaction, health insurance can improve service quality. This study aims to determine the relationship of service quality to the satisfaction of health insurance users of Inhealth Mandiri who visited the Kediri Service Office. The method of this research is analytic correlation with cross sectional model. The population used by all Mandiri Inhealth health insurance users visited Kediri Kediri Service Office on average in May, June, July 2017. The sampling technique used simple random sampling of 68 respondents. The independent variable of service quality and dependent variable is the satisfaction of health insurance user of Mandiri Inhealth who visited Kediri Service Office. Technique of collecting data using questioner then in test with rank spearman with significant level 5%. The results showed that most respondents (60%) said the quality of good service as many as 41 people and got the majority of respondents (56%) satisfaction level is very satisfied sebnyak 38 people. Based on spearman rank test, the value of r (0,000) <Î± (0,05) hence Ho's denotes that there is relation to the satisfaction of health insurance user of Mandiri Inhealth who visited Kediri Service Office. Better to maintain and improve the quality of service so that the health insurance user is very satisfied with the quality of service that has been provided by regularly evaluating the quality of service and the returning customer will be given a checklist of the services provided.